Investigation of changes in thickness and reflectivity from layered retinal structures of healthy and diabetic eyes with optical coherence tomography - Gao, Wei; Tátrai, Erika; Ölvedy, Veronika; Varga, Boglárka; Laurik, Lenke; Somogyi, Anikó; Somfai, Gábor Márk; DeBuc, Delia Cabrera (Journal of biomedical science and engineering, 2011)
OCT is usually employed for the measurement of retinal thickness. However, coherent reflected light carries more information characterizing the optical properties of tissue. Therefore, optical property changes may provide further information regarding cellular layers and early damage in ocular diseases. We investigated the possibility of OCT in detecting changes in the optical backscattered signal from layered retinal structures. OCT images were obtained from diabetic patients without retinopathy (DM, n = 38 eyes) or mild diabetic retinopathy (MDR, n = 43 eyes) and normal healthy subjects (n = 74 eyes). The thickness and reflectivity of various layered structures were assessed using a custom-built algorithm. In addition, we evaluated the usefulness of quantifying the reflectivity of layered structures in the detection of retinal damage. Generalized estimating equations considering within-subject inter-eye relations were used to test for differences between the groups. A modified p value of <0.001 was considered statistically significant. Receiver operating characteristic (ROC) curves were constructed to describe the ability of each parameter to discriminate between the eyes of DM, MDR and healthy eyes. Thickness values of the GCL + IPL and OPL showed a significant decrease in the MDR eyes compared to controls. Significant decreases of total reflectance average values were observed in all layers in the MDR eyes compared with controls. The highest AUROC values estimated for the total reflectance were observed for the GCL + IPL, OPL and OS when comparing MDR eyes with controls. Total reflectance showed a better discriminating power between the MDR eyes and healthy eyes compared to thickness values. Our results suggest that the optical properties of the intraretinal layers may provide useful information to differentiate pathological from healthy eyes. Further research is warranted to determine how this approach may be used to improve diagnosis of early retinal neurodegeneration.